2015
DOI: 10.1039/c5tc01536g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric power factor of Re-substituted higher manganese silicides with small islands of MnSi secondary phase

Abstract: Higher manganese silicides (HMS) are promising thermoelectric materials owing to the abundance of the constituent elements in the earth crust, environmental friendliness and good chemical stability at high temperatures. However, the metallic MnSi layers with a lateral size as large as B50 mm are formed in the melt-grown HMS samples. These large MnSi layers are characterized with relatively high electrical and thermal conductivities and low Seebeck coefficient, which can degrade the thermoelectric performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…Further studies have enhanced the peak zT values of GeTe‐based thermoelectric materials to a level higher than 2 . Under this temperature range (from ≈650 to ≈800 K), other p‐type thermoelectric materials, such as SnSe and higher manganese silicide have also drawn extensive research interests due to either low cost or high performance. Both Zhao et al and Liu et al have reported the peak zT value of SnSe can be higher than 2 when the temperature is above 800 K. Meanwhile, most other results suggest the peak zT values of SnSe are at the temperature range lower than 800 K .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies have enhanced the peak zT values of GeTe‐based thermoelectric materials to a level higher than 2 . Under this temperature range (from ≈650 to ≈800 K), other p‐type thermoelectric materials, such as SnSe and higher manganese silicide have also drawn extensive research interests due to either low cost or high performance. Both Zhao et al and Liu et al have reported the peak zT value of SnSe can be higher than 2 when the temperature is above 800 K. Meanwhile, most other results suggest the peak zT values of SnSe are at the temperature range lower than 800 K .…”
Section: Introductionmentioning
confidence: 99%
“…Mater. 2020, 32,1905703 [39,61,102,103] AgSeTe 2 , [104,105] GeTe, [106][107][108][109][110][111][112][113] SnSe, [34,35,40,45,47,[88][89][90]92,114] higher manganese silicide (HMS), [115][116][117] Cu 2 X (X = Te, Se, and S), [2,72,99,[118][119][120][121][122][123][124][125][126][127][128][129] PbX (X = Te, Se, and S), [30,[63][64][65][130][131][132]...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we report a combined experimental and theoretical study of the size effects on thermal transport in ∼20 nm thick ribbon structures of a representative complex crystal, higher manganese silicide (HMS), which is one of the leading thermoelectric materials made from earth-abundant, non-toxic elements 20,21 . Because of an advance in making clean electrical contact to suspended nanostructures, we are able to conduct four-probe thermoelectric measurements of the suspended nanoribbon and obtain the intrinsic thermal conductivity, which is considerably suppressed compared to the bulk values.…”
Section: Introductionmentioning
confidence: 99%
“…[106][107][108][109][110][111][112][113] Further studies have enhanced the peak zT values of GeTe-based thermoelectric materials to a level higher than 2. [108,[110][111][112] Under this temperature range (from ~650 to ~800 K), other p-type thermoelectric materials, such as SnSe [34, 35, 40, 45, 47, 88-90, 92, 114] and Higher Manganese Silicide [115][116][117] have also drawn extensive research interests due to either low-cost or high-performance. Both…”
Section: Introductionmentioning
confidence: 99%